1995
DOI: 10.1073/pnas.92.17.7714
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic methionyl aminopeptidases: two classes of cobalt-dependent enzymes.

Abstract: Using partial amino acid sequence data derived from porcine methionyl aminopeptidase (MetAP; methionine aminopeptidase, peptidase M; EC 3.4.11.18), a fulllength clone of the homologous human enzyme has been obtained. The cDNA sequence contains 2569 nt with a single open reading frame corresponding to a protein of 478 amino acids. The C-terminal portion representing the catalytic domain shows limited identity with MetAP sequences from various prokaryotes and yeast, while the N terminus is rich in charged amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
185
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(188 citation statements)
references
References 35 publications
2
185
1
Order By: Relevance
“…This line has amplified N-myc, which is characteristic of the most aggressive neuroblastomas seen in cancer patients (19). The CHP-134 tumor was staged at 200 mm 3 Reference residues include His-231, the residue alkylated by fumagilin and its semisynthetic derivatives (23), and Tyr-444, which terminates the 60-aa insert that forms a portion of the hydrophobic pocket of the MetAP2 active site. by twice-daily oral gavages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This line has amplified N-myc, which is characteristic of the most aggressive neuroblastomas seen in cancer patients (19). The CHP-134 tumor was staged at 200 mm 3 Reference residues include His-231, the residue alkylated by fumagilin and its semisynthetic derivatives (23), and Tyr-444, which terminates the 60-aa insert that forms a portion of the hydrophobic pocket of the MetAP2 active site. by twice-daily oral gavages.…”
Section: Resultsmentioning
confidence: 99%
“…PC-3 cells were inoculated in the flank of SCID male mice. Treatment was initiated when the tumors reached 150 mm 3 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methionine aminopeptidase type 2 is a cotranslational regulator of protein synthesis involved in N-terminal protein processing, and recent functional studies have demonstrated that this enzyme is an important molecular regulator of mammalian cell growth (20)(21)(22)(23). PPI-2458 is a potent inhibitor of the in vitro proliferation of activated human umbilical vein endothelial cells (HUVECs) and human fibroblast-like synoviocytes (FLS) from RA patients, both cell types that directly contribute to the pathogenesis of RA (18,23).…”
mentioning
confidence: 99%
“…The Zn atoms in the A. proteolytica aminopeptidase can be replaced in vitro with cobalt atoms, and like P. furiosus prolidase, is isolated with one metal ion per active site (Bennett and Holz 1997). Prior to the isolation of P. furiosus prolidase, the only other known naturally occurring Co-dependent enzymes from this family of enzymes were the methionine aminopeptidases (MAP), which also contain 2 Co 2+ per active site (Arfin et al 1995).…”
Section: C Structural Propertiesmentioning
confidence: 99%